Evaluation of Siltation Degree of Permeable Asphalt Pavement and Detection of Noise Reduction Degree - Shuang Chen; Xuechun Lin; Chuanfeng Zheng; Xuedong Guo; Wuxing Chen (Applied Sciences, 2020)
This study mainly uses PFC (particle follow code) to simulate the void characteristics of permeable asphalt mixture, and uses these to simulate the silting process. Then, a tire drop test was used to evaluate the noise reduction performance of permeable asphalt concrete. Finally, a self-made ring rutting test machine was used to simulate the silting process. Through experiments, the following conclusions were obtained: 1. The critical size of the sludge particle size is 0.3 mm–0.6 mm. 2. The quality of the water-permeable asphalt concrete specimens increased by 13% before and after silting, and the porosity of the specimens finally decreased from about 20% to about 8%. The water-permeable function only retained less than 20% of the original, and the water-permeable function was basically lost. 3. By measuring the road noise detection, it was found that the road noise is directly proportional to the degree of blockage of the permeable road. Compared with the original road with a perfect permeable function, the road noise of the completely blocked road increased by about 4 decibels. This study reveals the silting process of permeable asphalt mixture and the key particle size of the silt, which is of great significance for the detection, cleaning and maintenance of permeable asphalt pavements.